Enhanced cellulase enzyme production by Aspergillus niger using cellulase/iron oxide magnetic nano-composites - Durairaj Siva (Elsevier, 2022)
Objectives: The cellulase enzyme is used for various industrial applications such as textile, paper, food and biofuel industries. Industrially, the fungal strain, Aspergillus niger, is widely used to produce cellulase enzymes. Emerging evidence has indicated the possible role of magnetic nanocomposites in enhancing cellulase production by A. niger. The cellulase/iron oxide nanocomposites are already reported to be an eco-friendly method for modulating microbial biochemical characteristics. Methods: The present study was used to assess the efficacy of cellulase/iron oxide magnetic composites (CMNPS) for the enhanced production of cellulase enzyme. The fungal strain Aspergillus niger was isolated from the soil samples by using standard techniques. The fungi were then transfected with CMNPS and further evaluated for the production of cellulase enzyme. Results: Synthesis of the cellulase/iron oxide magnetic composites was characterized by UV, FTIR, and XRD. The produced CMNPS was used as substrate and enzyme production. The cellulase enzyme production by Aspergillus niger was analyzed by CMC (0.82 IU/ml enzyme activity) and FPA assay (0.039 IU/ml enzyme activity). CMNPS was also analyzed by CMC (0.74 IU/ml enzyme activity) and FPA assay (0.039 IU/ml enzyme activity). Reuse of CMNPS is the ultimate application and ecofriendly approach for the synthesis of cellulase enzymes. Conclusion: The study concludes that the cellulase/ iron oxide nanocomposites may be a useful tool for the enhanced production of cellulase enzyme from the soil fungus A. niger.